Effect of changing from the National Health and Nutritional Examination Survey III spirometry reference range to that of the Global Lung Initiative 2012 at Gold Coast Hospital and Health Service - Embling, Laura A. K.; Zagami, Debbie; Sriram, Krishna Bajee; Gordon, Robert J.; Sivakumaran, Pathmanathan (Journal of Thoracic Disease, 2016)
The categorisation of lung disease into obstructive ventilatory defect (OVD) and tendency to a restrictive ventilatory defect (TRVD) patterns using spirometry is used to guide both prognostication and treatment. The effectiveness of categorisation depends upon having reference ranges that accurately represent the population they describe. The Global Lung Initiative 2012 (GLI 2012) has spirometry reference ranges drawn from the largest sample size to date. This study aimed to determine whether using spirometry reference ranges from the new GLI 2012 dataset, compared to the previously used National Health and Nutritional Examination Survey III (NHANES III) dataset, resulted in a change in diagnosis between OVD, TRVD and normal ventilatory pattern (NVP). Spirometry data were collected from 301 patients, aged 18–80 years, undergoing investigation at the Gold Coast Hospital and Health Service (GCHHS) throughout February and March 2014. OVD was defined as a forced expiratory volume in 1 second (FEV1) divided by forced vital capacity (FVC) less than lower limit of normal (LLN). TRVD was defined as FEV1/FVC ≥ LLN, FEV1 < LLN, and FVC < LLN. The LLN values were determined by equations from the GLI and NHANES datasets. Spirometry interpreted using the NHANES III equations showed: 102 individuals (33.9%) with normal spirometry, 136 (45.2%) with an OVD pattern, 52 (17.3%) with a TRVD pattern, and 11 (3.7%) with a mixed pattern. When the spirometry data were interpreted using the GLI 2012 equations 2 (0.7%) individuals changed from OVD to NVP, 2 (0.7%) changed from NVP to OVD and 14 (4.7%) changed from TRVD to NVP. Using the GLI 2012 reference range resulted in a change in diagnosis of lung disease in 5.9% of the individuals included in this study. This variance in diagnosis when changing reference ranges should be taken into account by clinicians as it may affect patient management.